Проблемы процесса формирования денежных поступлений транспортных посредников - Романенко, Екатерина Михайловна; Романенко, Катерина Михайлівна; Romanenko, Ekaterina; Щелкунова, Анна Витальевна; Щелкунова, Анна Віталіївна; Shhelkunova, Anna (Одеса : Юрид. л-ра, 2012)
The article deals with the problems of obtaining income and award by forwarding and agent companies. The peculiarities, differences and common features of these problems are studied. On this basis a set of applicable methods of overcoming of the part of these problems is distinguished, as well as other measures of nstitutional character, which are aimed at their solving, are offered.
Романенко Е. М. Проблемы процесса формирования денежных поступлений транспортных посредников / Е. М. Романенко, А. В. Щелкунова // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 315-323.
Keywords: транспортные посредники; предприятия транспортного сервиса; транспортное экспедирование; агентирование; вознаграждение экспедитора; вознаграждение агента; формирование денежных поступлений; транспортні посередники; підприємства транспортного сервісу; транспортне експедирування; агентування; винагорода експедитора; винагорода агента; формування грошових надходжень; freight forwarders; transport service enterprises; transport forwarding companies; agency services; award of the freight forwarder; award of the agent; formation of incomes